Newly recorded genera and species of the subfamily Nolinae, with the description of a new species of Njalkanola László, Ronkay & Witt from China (Lepidoptera: Noctuoidea: Nolidae) - Ruan, Zan-Yu; Yu, Yong; Hu, Yan-Qing (Zootaxa, 2024)
Five genera of Nolinae (Njalkanola László, Ronkay & Witt, 2010, Barnanola László, Ronkay & Witt, 2010, Calonola László, Ronkay & Witt, 2010, Toerpenola László, Ronkay & Witt, 2010 and Cornuanola László, Ronkay & Ronkay, 2013) are reported from China for the first time. A new species of Njalkanola (Njalkanola puerensis Ruan, Yu & Hu, sp. nov.) is described from Yunnan Province of China. Detailed illustrations of adult and genitalia are provided.